Pengembangan Sistem Automatic Sliding Adaptive Two Axis Pada Mesin Pengelasan Smaw - Nainggolan, Johannes Riomanto; yohanes, yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Welding of automatic sliding adaptive two-axis systems is defined as welding Automatic with equipment that has a control system that automatically determines changes in welding conditions and acts under the equipment with adjustable actions to make adjustments to SMAW 1G and 1F welding positions. In the development of this study using the development method of DFMA (Desing for production and assembly) that can be interpreted as the design of a product or component that can facilitate the production process and the assembly process with other components to become a product unit. This welding uses the X and Y coordinate system. An axis is used to control the movement of the space in the X direction. The other is to move the perpendicular position in the direction of the Y axis. In addition, two opposite coordinate systems can be activated to apply two-way growth together welding. The development of sliding adaptive two-axis machines includes the design, manufacture of tools, testing of sliding adaptive two-axis machines, and testing of welding results based on visual savings and penetrant testing. The parameters are used are hem of v with an angle of 60, the current uses 90 Amper and the welding speed controlled by Arduino Uno with 4.34 rpm stepper motor, the material used is low-carbon steel. Liquid penetration tests are performed on 3 samples, the least of which are welding defects, namely in sample A compared to sample C.Keywords : SMAW Welding, Sliding Adaptive Two-Axis, Penetrating Tests